The Effect Of Pacifier Use (Non-Nutritive Sucking) On Pain Intensity In Premature Babies Undergoing IV Infusion In The NICU And Perina Room Alia Hospital Jakarta - Irmawati, Irmawati; Hanik Rohmah Irawati (Sean Institute, 2025)
Premature babies are susceptible to various health complications due to immaturity of the organ system, so they need intensive care, namely NICU. Babies will experience pain due to invasive procedures. This pain can be treated with non-pharmacological methods, namely Non-Nutritive Sucking (NNS) in the form of pacifiers. This study aims to determine the effect of pacifier use (non-nutritive sucking) on pain intensity in premature babies who have an IV in the NICU and Perina Alia Hospital Jakarta. This study used a quasi-experimental method with a post-test-only non-equivalent control group approach. The study sample consisted of 34 respondents divided into intervention and control groups, each with 17 respondents. The sampling technique used purposive sampling. The pain scale measurement instrument used NIPS (Neonatal Infant Scale). The average pain intensity of the intervention group was 1.65 and the control group was 4.24. Data analysis used the independent T-test. The results of the study obtained a p value = 0.001 (a <0.05) meaning that there is an effect of pacifier use (Non- Nutritive Sucking) on pain intensity in premature infants who underwent IV in the NICU and Perina Alia Hospital Jakarta. Pacifiers are recommended as an independent nursing intervention in reducing pain intensity in infants who underwent IV.